2001
DOI: 10.1074/jbc.m011376200
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition of Chlamydomonas reinhardtii in State 1 and State 2

Abstract: The relationship between state transitions and photoinhibition has been studied in Chlamydomonas reinhardtii cells. In State 2, photosystem II activity was more inhibited by light than in State 1. In State 2, however, the D1 subunit was not degraded, whereas a substantial degradation was observed in State 1. These results suggest that photoinhibition occurs via the generation of an intermediate state in which photosystem II is inactive but the D1 protein is still intact. The accumulation of this state is enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 58 publications
(50 reference statements)
3
7
0
Order By: Relevance
“…We also confirmed that the acceleration of the CBP diffusion occurred in the membranes isolated from the wild-type cells incubated anaerobically in the dark (Fig. S5), which is an alternative method to induce state 2 condition in C. reinhardtii 32. This also verified the acceleration of the CBP diffusion caused by another LHCII phosphorylation-induced condition.…”
Section: Resultssupporting
confidence: 82%
“…We also confirmed that the acceleration of the CBP diffusion occurred in the membranes isolated from the wild-type cells incubated anaerobically in the dark (Fig. S5), which is an alternative method to induce state 2 condition in C. reinhardtii 32. This also verified the acceleration of the CBP diffusion caused by another LHCII phosphorylation-induced condition.…”
Section: Resultssupporting
confidence: 82%
“…This drop in the effective quantum yield of PSII had already been noted by Antal et al. (2003), who interpreted it as the consequence of a transition from state 1 to state 2 of the photosynthetic apparatus (Finazzi et al. 2001).…”
Section: Resultssupporting
confidence: 57%
“…This pathway can be induced by warming above 30°C, in the same way as the cyclic electron flow and the heat-induced state 1 to state 2 transition. State 2 appears to switch on the cyclic electron pathway, which would play a protective role against photoinhibition (Finazzi et al 2001(Finazzi et al , 2002. The quinone dark-reduction pathway can be also induced by high light and various stress conditions, modifying the AG emission (Janda et al 1999).…”
Section: Resultsmentioning
confidence: 98%